Acceptance of COVID-19 vaccine and its determinants: evidence from a large sample study in Bangladesh. Issue 6 (June 2021) - Akiful Haque, Miah Md.; Rahman, Mohammad Lutfor; Hossian, Mosharop; Matin, Kazi Farhana; Nabi, Mohammad Hayatun; Saha, Shuvajit; Hasan, Mehedi; Manna, Ridwana Maher; Barsha, Sabrina Yesmin; Hasan, S.M.Rezwanul; Siddiquea, Saleka Raihana; Rahman, Mahfil Ara; et al.
Abstract: Aim: Our study aimed to understand the acceptance level of the COVID-19 vaccine and its determinants among the adult Bangladeshi population. Methodology: This cross-sectional study was conducted in all eight divisions of Bangladesh. Data from 7, 357 adult respondents were collected between January 17 and February 2, 2021, using a self-administered semi-structured questionnaire. Statistical software STATA (Version 16.1) was used for all analyses. Results: The majority of study participants were from the Dhaka division (34.24%). The most common age group was ≤30 years (46.18%). Almost two-thirds of respondents were male (65.50%) and married (67.76%). A large portion (79.85%) of people who had positive vaccine intentions believed that vaccination should be made mandatory for everyone. The majority of the respondents thought that the vaccine would work against COVID-19 infection (67%). In the binary logistic regression analysis, participants who had the education level of graduation or above (AOR = 1.80), age ≥50 years (AOR = 1.97), students (AOR = 2.98), monthly income ≥41, 000 BDT (AOR = 2.22), being resident of rural area (AOR = 2.24), respondents from Khulna division (AOR = 6.43) were more likely to receive a COVID-19 vaccine. Those who had family members diagnosed with COVID-19 (AOR = 1.24), presence of chronic disease (AOR = 0.72), and those who were vaccinated in the last few years (AOR = 1.32) were also more likely to accept the COVID-19 vaccine. Conclusion: Most of the respondents were willing to be vaccinated based on the belief that the vaccine will work against COVID-19. As rumors are generating daily, there is a need for policy-level initiative and evidence-based mass media promotion to keep inspired the general Bangladeshi people to accept the COVID-19 vaccine whenever it will be available at the individual level. Abstract : COVID-19; Vaccine; Acceptance; Hesitancy; Bangladesh.